2010
DOI: 10.1111/j.1365-2133.2010.09988.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure to hair dye induces regulatory T cells in mice

Abstract: This study shows that PPD-containing hair dyes strongly affect the immune system. In addition to being potent skin sensitizers that activate inflammatory T cells, hair dyes also induce anti-inflammatory mechanisms. This might explain why many consumers can use hair dyes repeatedly without developing noticeable allergies, but it also raises the question whether the immune modulatory effects of hair dyes might influence the development of autoimmune diseases and cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…As children and teenagers also dye their hair, a similar disease spectrum is encountered in these groups (16). Besides the severe cutaneous and respiratory complications, the potential systemic consequences of contact allergy to hair dyes are currently unknown (17,18).…”
mentioning
confidence: 99%
“…As children and teenagers also dye their hair, a similar disease spectrum is encountered in these groups (16). Besides the severe cutaneous and respiratory complications, the potential systemic consequences of contact allergy to hair dyes are currently unknown (17,18).…”
mentioning
confidence: 99%
“…21 Due to hypersensitivity, allergy reaction, and immune response, permanent hair dyes such as PDA and its related chemicals have been widely investigated. [1][2][3][4][5] Since PDA or its related chemicals are used more extensively than oxidative hair dyes, their immune-toxicity, carcinogenesis, and genetic toxicity is problematic to human skin keratinocyte cells. 4,5 Mosley-Foreman et al 3 reported that permanent hair dye revealed cytotoxicity against human skin keratinocyte cells under light irradiation, and no chemical structure-related phototoxicity of derivatives of PDA was found.…”
Section: Discussionmentioning
confidence: 99%
“…1 In particular, consumer-available PDA-containing hair dyes are known to be potent immune activators that lead to increased inflammatory cytokines. 2 Furthermore, PDA may cause deoxyribonucleic acid (DNA) cleavage or gene toxicity against human skin keratinocyte cells under light irradiation. 3 Derivatives of PDA chemicals are known to induce DNA damage and carcinogenic reactions in human skin keratinocyte cells.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the exposure regime also seems to play a critical role in the immune response induced by hair dye. Using an experimental set‐up in which mice were repeatedly exposed to the hair dyes every second week for a total of 10 weeks, we found that both PPD‐containing and PTD‐containing hair dyes still induced an immune response, albeit to a lesser extent than seen with the modified version of the LLNA . The explanation for this seems to be that, in addition to proinflammatory mechanisms, repeated hair dye exposure also induced anti‐inflammatory mechanisms, such as regulatory T cell and skin IL‐10 production .…”
Section: Effects Of Mixing Contact Allergensmentioning
confidence: 92%